2013
DOI: 10.1039/c3ta12925j
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing highly ordered mesoporous carbon–silica composite thin films

Abstract: Free-standing mesoporous carbon-silica composite films with different silica contents are successfully prepared with a crack-free morphology, square centimeter size, and a highly ordered mesostructure. The films are first synthesized on Al 2 O 3 -coated Si substrates by spin-coating of a tri-constituent solution, in which triblock copolymer Pluronic F127, resin and tetraethoxylsilane (TEOS) are used as the template, carbon and silica precursors, respectively. After the organic-inorganic assembly, calcination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Mesopore sizes and mesostructures can be controlled by the template or by the composition of the template/carbon precursor mixture rendering soft‐templating a highly versatile method for synthesis of carbon thin films with a wide range of properties. Furthermore, the same group has shown that ordered mesoporous silica/carbon composite films can be synthesized by spin coating of a mixture of triblock copolymer Pluronic F127 (surfactant), resin (carbon precursor) and tetraethoxylsilane (silica precursor) on Al 2 O 3 ‐coated Si substrates (Figure B,C) . After carbonization and removal of the substrate as well as the silica part of the composite (acting as secondary hard template), free‐standing carbon films with significantly enhanced specific surface areas exceeding 2000 m 2 g −1 are obtained.…”
Section: Controlled Synthesis Of Nanoporous Carbon Thin Films and Appmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesopore sizes and mesostructures can be controlled by the template or by the composition of the template/carbon precursor mixture rendering soft‐templating a highly versatile method for synthesis of carbon thin films with a wide range of properties. Furthermore, the same group has shown that ordered mesoporous silica/carbon composite films can be synthesized by spin coating of a mixture of triblock copolymer Pluronic F127 (surfactant), resin (carbon precursor) and tetraethoxylsilane (silica precursor) on Al 2 O 3 ‐coated Si substrates (Figure B,C) . After carbonization and removal of the substrate as well as the silica part of the composite (acting as secondary hard template), free‐standing carbon films with significantly enhanced specific surface areas exceeding 2000 m 2 g −1 are obtained.…”
Section: Controlled Synthesis Of Nanoporous Carbon Thin Films and Appmentioning
confidence: 99%
“…The inset in (e) shows structural models of the mesochannel orientation. C) Synthesis process for free‐standing mesoporous carbon–silica composite thin films, silica films, and carbon films by using a coating‐etching approach (B,C) reproduced with permission . Copyright 2013, the Royal Society of Chemistry.…”
Section: Controlled Synthesis Of Nanoporous Carbon Thin Films and Appmentioning
confidence: 99%
“…[1][2][3][4] Although the microporous carbons hold very high surface areas and pore volumes, their pore structures are uncontrollable and the pores are mainly contributed by micropores (< 2 nm), which are not favorable for quick electrolyte ion diffusion. 3,[8][9][10] In this regard, numerous techniques were developed to fabricate mesoporous carbons with diverse structures (films, 11-14 spheres [15][16][17] or free fibers 2,[18][19][20][21][22], including nanocasting, 14,16 soft-templating methods, 10,15,17,23,24 and so on. 3,[8][9][10] In this regard, numerous techniques were developed to fabricate mesoporous carbons with diverse structures (films, 11-14 spheres [15][16][17] or free fibers 2,[18][19][20][21][22], including nanocasting, 14,16 soft-templating methods, 10,15,17,23,24 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, enhancement in permittivity below the percolation threshold and/ or a drastic increase in permittivity at the percolation threshold were observed in polymeric composites filled with conductive particles, such as metal or carbon, 20) 30) and aerogel composites. Si et al 31) and Hübert et al 32) reported the preparation and the electrical conductivity of carbon-silica porous nanocomposites. However, none of these previous studies reported dielectric properties.…”
Section: )13)mentioning
confidence: 99%